Theaflavin-3, 3′-Digallate Suppresses RANKL-Induced Osteoclastogenesis and Attenuates Ovariectomy-Induced Bone Loss in Mice - Ai, Zexin; Wu, Yang’ou; Yu, Miao; Li, Jia; Li, Shengjiao (Frontiers in Pharmacology, 2020)
Theaflavin-3, 3′-digallate (TF3) is extracted from black tea with strong antioxidant capabilities. The aim of our study was to value the impacts of TF3 on osteoclastogenesis and investigate the underlying mechanisms. TF3 efficiently decreased receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclasts formation and reactive oxygen species (ROS) generation in a dose-dependent manner. Mechanistically, TF3 reduced ROS generation by activating transcription factor nuclear F-E2-related factor 2 (Nrf2) and its downstream heme oxygenase-1 (HO-1), and inhibited the mitogen-activated protein kinases (MAPK) signaling. Besides, micro-CT analysis, H&E staining and TRAP staining of the femurs from C57BL/6J female mice showed that TF3 was positively attenuated bone loss and osteoclastogenesis in mice. Immunofluorescence staining, 2′,7′-dichlorofluorescein diacetate (DCFH-DA) staining and measurement of malonaldehyde (MDA) and superoxide dismutase (SOD) showed that TF3 increased the expression of Nrf2 and decreased the level of ROS in vivo. These findings indicated that TF3 may have potential to treat osteoporosis and bone diseases related to excessive osteoclastogenesis via inhibiting ROS level.